Milk production on cattle farms in the lower Guayas basin, Ecuador - Medina Pinoargote, Gabriela Electra; Pereda Mouso, Jorge Jesús; Curbelo Rodríguez, Lino Miguel; Pedraza Olivera, Redimio Manuel (Cuban Journal of Agricultural Science, 2026)
To characterize the milk production potential on cattle farms in the lower Guayas basin, in Ecuador, a sample of 70 farms was formed and a survey that integrated structural variables was applied. A principal component analysis was performed, with the most important variables in the first two components. A cluster analysis was applied, in which three clusters were obtained, each considered a category of milk production potential. The categories were named low (I), medium (II) and high milk production (III). To validate the results and determine differences between the categories, a canonical discriminant analysis was performed. The study showed that the variables in order of priority were located in four components and were related to milk production, management, inputs, and costs. When comparing categories, there were problems with reproduction, with low coefficients of variation. The remaining variables exceeded 50 % and confirmed the heterogeneity that existed in the management and dimensions of the farms. There were statistical differences between the categories, which were determined, firstly, by the calving-calving interval, days open, milking cows, and females in the herd. The categories that characterized the milk production potential on cattle farms in the lower Guayas basin were obtained, which showed statistical differences determined by reproduction and herd management.